Pengokohan Keterampilan Menulis Artikel Popular Melalui Model Pembelajaran Berbasis Proyek Dan Evaluatif Bagi Mahasiswa Prodi Pendidikan Bahasa Arab Universitas Islam Malang - Sultan Sultan (Cordova Journal, 2023)
The argument for writing this article is to respond to students' problems in learning to write popular articles which are part of the study in Indonesian language courses as a general compulsory subject in tertiary institutions. The method used in completing this research is a portfolio-based descriptive qualitative method. The results of this study show that first, the process of strengthening popular article writing skills through project-based learning for PBA UNISMA students is carried out in several processes, namely the planning phase, the creation phase, and the processing phase. The results of the process evaluation show very well. then secondly, the results of the evaluation of project-based learning in strengthening popular article writing skills show optimal results, this is evidenced by the average value of 84.6, project-based learning shows positive results.